(untitled) (Economic studies journal, 2023)
This work aims to revolutionize the selection process of online conferencing and video-sharing applications within Libyan universities by introducing an innovative framework. This framework utilizes the methodologies of Prompt Engineering and the Grey-based approach to provide a systematic decision-making technique. It carefully considers the unique needs of Libyan universities and the prevailing conditions in Libya, thereby enabling decision-makers to make well-informed choices and optimize their technological infrastructure. By harnessing the cutting-edge methodology of Prompt Engineering and leveraging the power of the Grey-based approach, we introduce a systematic decision-making technique that takes into account the distinct requirements of Libyan universities and the prevailing conditions in Libya. To date, no literature has been discovered that combines Prompt Engineering and the Grey-based approach. However, we have developed a novel framework that integrates both methodologies, offering a systematic and flexible evaluation approach for the selection of appropriate platforms within Libyan universities. This framework also effectively addresses the uncertainties present in real-world situations while considering the specific needs of Libyan universities.